Peran Kejujuran Akademik (Academic Honesty) dalam Pendidikan Karakter Studi Pada Mahasiswa Jurusan Bimbingan Konseling Islam Fakultas Ushuludin Adab dan Dakwah Angkatan 2013/2014 - Fitri Sukmawati (Khatulistiwa, 2016)
Academic Honesty among students of the Department of Islamic Guidance and Counseling in the Faculty of Ushuludin Adab and Dakwa class of 2013/2014, there are still many who commit academic dishonesty or cheating. The causes of cheating behavior comes from the students themselves and the outside or external factors. For example, a lack of awareness and independence in learning among students as well as lazy behavior that is still part of the students’ personality. This behavior is a barrier to support character education that serves as educational goals.